Cobalt-catalyzed synthesis of bromomonofluoroallyl ketones by addition of alkynes and α-bromo-α-fluoroketones. (2nd March 2021) - Ren, Jie; Fu, Xiaoyi; Hou, Yali; Wu, Jingjing; Wu, Fanhong
Graphical abstract: Highlights: The first example of Co-catalyzed monofluoroalkylation of alkynes with α-bromo-α-fluoroketones was established. The reactions were accomplished at room temperature, which is mild and efficient. This method demonstrated broad substrates scope. An new strategy for the synthesis of bromomonofluoroallyl ketones. Abstract: The first example of Co-catalyzed monofluoroalkylation of alkynes with α-bromo-α-fluoroketones was established for the synthesis of a variety of bromomonofluoroallyl ketones. The reactions were successfully accomplished at room temperature, which were mild and efficient. The mechanism investigation showed that a radical pathway was involved.